Bogie Frame Structure Evaluation for Light-Rail Transit (LRT) Train: A Static Testing - Djoko Wahyu Karmiadji; Budi Haryanto; Ogi Ivano; Mustasyar Perkasa; Abdul Rohman Farid (Automotive Experiences, 2021)
A new bogie frame of Light-Rail Transit (LRT) is having its strength of structure verified with experimental static testing according to EN 13749 standards. Static testing of bogie frame structure of LRT is performed by using a combination of seven tensile and compression loads that comprise of operational loads (normal service) and over-loads (exceptional service). Measurement parameters of bogie frame are strain and deflection values. The strain and deflection values resulted at every step of the load test were measured and monitored to further be used as analytic data. This data is then compared to the stress data of finite element analysis to check its deviation value. Testing results show the maximum stress value is 81.48 MPa on operational load, meanwhile, for exceptional load case, maximum stress is 120.96 MPa and deflection value is 1.25 mm. The maximum stress value is still below yield strength of bogie frame material S 555J2 (ï³y=355 MPa). According to testing data, structure of bogie frame LRT fulfill as the acceptance criteria.